2016
DOI: 10.1021/acs.jpca.6b00543
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure and Bonding in Plutonium Carbides: A Theoretical Study of PuC3

Abstract: The most relevant species of plutonium tricarbide were characterized using theoretical methods. The global minimum is predicted to be a fan structure where the plutonium atom is bonded to a quasi-linear C 3 unit. A rhombic isomer, shown to be a bicyclic species with transannular C−C bonding, lies about 39 kJ/mol above the fan isomer. A linear PuCCC isomer and a three-membered ring CPuC 2 isomer were found to be higher in energy (150 and 195 kJ/ mol, respectively, above the predicted global minimum). The possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
(67 reference statements)
1
7
0
Order By: Relevance
“…In most cases, the T1 values do not indicate a strong multireference character of the wave functions, as shown in Table S4. Previous studies 10,22 on actinide carbide compounds have also shown that the results of multiconfigurational calculations are consistent with those of CCSD(T). Our results indicate that the CCSD(T) method predicted a different energy order in comparison to B3LYP.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…In most cases, the T1 values do not indicate a strong multireference character of the wave functions, as shown in Table S4. Previous studies 10,22 on actinide carbide compounds have also shown that the results of multiconfigurational calculations are consistent with those of CCSD(T). Our results indicate that the CCSD(T) method predicted a different energy order in comparison to B3LYP.…”
Section: Resultssupporting
confidence: 74%
“…The single-point energies were also calculated using coupled cluster theory with single and double excitations and a perturbative triples correction (CCSD­(T)) to obtain a more reasonable energy order for the different isomers. Previous works , have indicated that CCCD­(T) can predict energy order similarly to the multireference configuration interaction (MRCI), and these works have also shown that the spin–orbit coupling (SOC) produces low incremental energy difference. The SOC was not considered to evaluate the energy order for the different isomers in the present work.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, only four theoretical studies dealt with AnC molecules (UC, 19,20 NpC, 21 and PuC 22 ) until now, providing very limited information on their molecular properties. In contrast, the di-, 21,[23][24][25][26] tri-, 27,28 and tetracarbides 18,20,21,29 of Th, U, Np, Pu, and Am have been quite extensively explored by advanced quantum chemical calculations. The lack of reliable information on the monocarbides is the motivation to our present study in which we apply relativistic multireference and density functional theory (DFT) methods to elucidate the electronic structure and other molecular characteristics of the most important monocarbides (ThC, UC, PuC, and AmC).…”
Section: Introductionmentioning
confidence: 99%
“…23 The UC 3 and PuC 3 clusters from global-minimum searching results adopt fan-like structures via the bonding of actinides to the C 3 unit. 24,25 From then on, the actinide tetracarbide clusters (AnC 4 , An: Th, U, Np, Pu, and Am) and actinide hexacarbides (ThC n , UC 6 and PuC 6 , n = 1− 7) have been theoretically predicted to possess a planar sector structure in which actinide atoms are connected to fan-shaped C 4 and C 6 , respectively. 22,26−30 Although a series of gas-phase molecular species, like An m C n + (m = 2, n = 2−18, An = Th, U) have been produced by laser ionization of AnC 4 alloys, only An 2 C 3 and An 2 C 4 have been structurally assigned, 31 atom.…”
Section: Introductionmentioning
confidence: 99%
“…The ground states for actinide monocarbides have been predicted by relativistic multireference calculations as 3 Σ + , 4 H, 5 H, 7 F, and 3 Σ + for AnC (An: Th, U, Np, Pu, and Am), respectively. , The UC 2 was identified as being a linear CUC molecule and the bent ThC 2 are energetically favored . The UC 3 and PuC 3 clusters from global-minimum searching results adopt fan-like structures via the bonding of actinides to the C 3 unit. , From then on, the actinide tetracarbide clusters (AnC 4 , An: Th, U, Np, Pu, and Am) and actinide hexacarbides (ThC n , UC 6 and PuC 6 , n = 1–7) have been theoretically predicted to possess a planar sector structure in which actinide atoms are connected to fan-shaped C 4 and C 6 , respectively. , Although a series of gas-phase molecular species, like An m C n + ( m = 2, n = 2–18, An = Th, U) have been produced by laser ionization of AnC 4 alloys, only An 2 C 3 and An 2 C 4 have been structurally assigned, which contain An–C 2 bonds similar to those in U­(C 2 ) 2 and U­(C 2 ) 3 molecules produced by the reaction of the U atom and carbon atom . Hitherto, except that experiments in gas phase often result in fullerenes, , there are no other molecular actinide carbides reported.…”
Section: Introductionmentioning
confidence: 99%